UTILIZATION OF COCONUT LEAVES WASTE TO BECOME INGKE STICK PLATE - Muanah Muanah; Suwati Suwati; Nur Annisa Istiqamah; Suhairin Suhairin; Marianah Marianah; Basirun Basirun (Universitas Djuanda Bogor, 2023)
West Lombok is one of the regencies with the largest coconut producer in West Nusa Tenggara. The prioritized priority is young coconuts and old coconuts, usually for the coconut milk to be taken and direct consumption for vegetables and wet snacks. In addition to the fruit that people rarely know that also has potential, namely the bones of the leaves or often called sticks, these leaves are both dry and wet at the same time they are also harvested but not utilized. So seeing its considerable potential, assistance is provided to improve the skills and income of the community in Taman Sari Village through the making of ingke (stick plates). The mentoring method consists of 3 stages, namely counseling, training, and evaluation. The main target of this mentoring activity is mothers who live in the village of Ataman Sari, West Lombok. The results of the mentoring show that the activity was attended by 25 people with a companion team of 5 people so that each handled 5 participants. After the activities were carried out it was proven to be able to increase the knowledge of 75% and the skills of the community by 70% and in addition to knowledge and skills they were also able to make ingke independently. Inke produced not only for personal use can also be sold for additional income. The results of the evaluation show that the community needs to be assisted in the creation of other ingke plates so that the production results are more diverse.